Gambaran Retensi Perawat Pelaksana Di Rumah Sakit - Kartika Ekawati; Muhammad Hasib Ardani (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
Nurse retention is a process that refers to the ability of an organization to maintain nurses within a maximum period of time. This hospital has a high nurse retention rate with a turnover rate of 7% in the past year. This study aims to determine the description of nurse retention. This research was a quantitative descriptive study with a survey approach. The research sample consisted of 110 executing nurses of a hospital in Semarang. The research instrument used a questionnaire with 18 questions. The results show that nurse retention on the autonomy and freedom dimensions are considered good by 92.7% nurses, the dimensions of work compatibility factors is considered good by 84.5% nurses, the dimensions of work support and recognition are considered good by 76.4% nurses, compensation dimensions and career growth are considered good by 75.5% nurses, and organizational culture dimensions are considered good by 51.8% nurses. It is suggested that the hospital to be more open to receive suggestions for improving services in order to increase nurse retention.